Severe combined immunodeficiency and adenosine deaminase deficiency: failure of enzyme replacement therapy. Issue 6 (June 1980) - Ziegler, J B; Lee, C H; Van der Weyden, M B; Bagnara, A S; Beveridge, J
Abstract : A first-born baby boy presented at age 3 months with persistent diarrhoea, failure to thrive, and recurrent bacterial and fungal infections. Severe combined immunodeficiency was demonstrated. A deficiency of adenosine deaminase (ADA) activity was suggested by the presence of extensive skeletal abnormalities, and the ADA activity in erythrocyte and leucocyte lysates was < 0.005 nmol/h per mg protein. Culture of ADA-negative peripheral blood mononuclear cells, together with purified calf ADA, did not alter the absent phytohaemagglutinin response. Treatment with immunoglobulin, pentamidine, and co-trimoxazole was started and a programme of ADA enzyme replacement, with infusions of plasma and frozen irradiated erythrocytes, was begun at age 4 months and achieved blood ADA levels in excess of 30 nmol/h per mg haemoglobin. Although resolution of the interstitial pneumonitis and skeletal abnormalities was observed, there was no evidence of immunological reconstitution. The patient died at age 17 months after a parainfluenza pneumonitis. Features of importance in predicting lack of benefit from enzyme replacement by erythrocyte infusion in ADA-negative severe combined immunodeficiency appear to be early clinical presentation with associated severe skeletal abnormalities, a very low level of residual ADA activity in peripheral blood mononuclear cells, and lack of effect of exogenous ADA on the absent in vitro mitogen response of ADA-negative blood mononuclear cells.